PENGARUH STATUS GIZI KURANG PADA PENDERITA TERHADAP KEGAGALAN PENGOBATAN TUBERKULOSIS PARU DI B.P.4 SEMARANG - Anna Theresia Regina Ritonga; Winarto -; M. Sulchan (Jurnal Kesehatan Masyarakat Indonesia, 2005)
Introduction. l'r/HO predicted that there would be 591.000 new Tuberculosis cases in 2001. Tuberculosis is the second leading cause ofdeath out of t3 leading causes in Indonesia. Nutritional status, social economic condition, and level at education play vital role to cure Tuberculosis. Objective: to find out correlation between patient' nutrientdeficiencis and the failure to cure pulmonary Tuberculosis.Methods. The design was a Case Contro[ Sutty, with pTB (Pulmonary Tuberculosis) patientsfrom 8.P.4 Semarangfrom 1998 to 2000 as sample with a total ofihtrty -five patient as cases and forty - seven patient as control. Data were collected include patient weight, height, age,-sex, marital status, level of education and income.. Result. There was no significant dffirence in witght at the biginntng . of treatment between cases and control ( p:0,1 ), but there was a significant difference in ieight at the end if ".treatment ( p=0,04 ).There was no significant dffirence in weight changes in patients between cases and controls l (p:0,4 ) and also occured to the beginning of nutritional status ( p=0,1 ) and at the end ( p:0,3 ).Further results from analysis had shown that patient with nutrient' deficiency at the beginning had 3.4 times more risks to have failure in curing proses since nutrient is the most significant factor compared to others. Conclusion. Nutritional status particularly at the beginning of treatment is very influential to PTB treatment. It is suggested to pay attention topatimt' nutritional stafus during the treatment, particularly at the beginning phase of treatment. Advancetl stutly - which is more spesific is'needed to find out some nutritional roles to the success of Tuberculosis treatment.Keyword : nutritional status, Pulmonary Tuberculosis, weight